Wolność jako zasada neokonstytucjonalna - Holocher, Justyna (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2018)
The liberal principal in dubio pro libertate is the philosophical foundation of the theory of constitutional rule of law and constitutes an incorporation of moral principles into the law and order. It is perceived as a circumstance to confirm the legitimacy for the thesis of passing from rule of law to the constitutional rule of law on the philosophical and dogmatic planes. It influences the process of constitutionalization, and especially the rules governing the judicial interpretation, forming thus the legal theory of interpretation built upon the argumentative nature of the law and its weight-based application which is essentially a matter of selecting the rule applicable as the parameter of control of constitutionality. It bolsters up constitutionalism conceived as a set of legislative measures aimed at limiting the legislative authority and jurisprudence by attaching a particular importance to the liberty arguments whose value will be eventually referred to the good of the individual.
Liberty as a neoconstitutional principle
Keywords: neoconstitutionalism; liberalism; liberty; pluralism; weighing of values